ASPECTS REGARDING THE NEW CLASSIFICATION OF PERIODONTAL DISEASES - Sorina Mihaela Solomon; Irina Georgeta Sufaru; Liliana Pasarin; Silvia Martu (Romanian Dental Association for Education, 2019)
The 2017 World Workshop Classification system for periodontal and peri-implant diseases and conditions was developed in order to accommodate advances in knowledge derived from both biological and clinical research, that have emerged since the 1999 International Classification of Periodontal Diseases. The result is a redesigned disease classification framework that guides comprehensive treatment planning and allows for a personalized approach to patient care. Highlights from the updated classification include a multi-dimensional staging and grading system for periodontitis classification, a recategorization of various forms of periodontitis, and the inaugural classification for peri-implant diseases and conditions. Of extreme importance, the new classification includes clinical health for the first time, and distinguishes an intact and a reduced periodontium throughout. Also, the term 'aggressive periodontitis' was removed, creating a staging and grading system for periodontitis that is based primarily upon attachment and bone loss and classifies the disease into four stages based on severity (I, II, III or IV) and three grades based on disease susceptibility (A, B or C).